Structural and Finite Element Analysis of Steering Yoke of an Automobile - A. B. Nitalikar; Prof. R. D. Kulkarni; Prof. A. Z. Patel (International Journal of Engineering and Management Research, 2020)
This paper postulates the study of the structural analysis of steering yoke. In a steering system, steering column is one of the main device of an automobile. It is a very important to attain stability and steady movement of vehicle. The core part of steering column is manufactured through various processes such as hot forging, machining and assembly by welding. Power transmission system of vehicle consist several components which sometimes suffer from different stresses (failures) While a generalized case shall be taken up for study while pursuing dissertation work on this topic, the findings are expected to throw light on the causes, location and extent of stresses on the parts in the sub-assembly In this study, the nature and characteristics of stresses acting on the component by using software tools (for simulation/analysis) are carried out.